Cross-Ladder Diagrams Via Hierarchical Equations in the Light Front - Sales, Jorge Henrique; Suzuki, Alfredo Takashi [UNESP]; Santos, Gislan S.; Lima, Cassio A. (Springer, 2015)
We calculate the correction to the propagator of two bosons up to the g (4) order in the cross-ladder approximation in the light front. The hierarchy of the coupled equations describe the propagator of two bosons in various cases, including the cross-ladder approximation. Our results show that the contribution of the pair is small and is limited to a range of bound state.